2021
DOI: 10.3390/plants10061166
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Sesame Mutants Tolerant to Severe Drought Stress during Germination and Early Seedling Growth Stages

Abstract: In the context of climate change and water scarcity, there is a need to develop and use drought-tolerant sesame cultivars. This study was conducted to evaluate the response of 13 sesame genotypes, including 11 mutants and their wild-types, to drought during germination and early seedling growth. Moderate and severe drought stress was simulated by applying polyethylene glycol (PEG) at two osmotic potentials, −0.6 MPa and −1.2 MPa, respectively, on seeds of two successive mutant generations, M2 and M3. The param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 37 publications
1
5
0
1
Order By: Relevance
“…The VI and GI are highly sensitive to drought and can be considered as effective indicators of drought tolerance in plants [70,71]. Our research results indicated that PEG stress generally decreased the GI and VI of the five species of Clematis (Table 1), as is consistent with previous studies on Triticum aestivum [72], Cicer arietinum [73], Sesamum indicum [70], and other plant species [65,74].…”
Section: Discussionsupporting
confidence: 91%
“…The VI and GI are highly sensitive to drought and can be considered as effective indicators of drought tolerance in plants [70,71]. Our research results indicated that PEG stress generally decreased the GI and VI of the five species of Clematis (Table 1), as is consistent with previous studies on Triticum aestivum [72], Cicer arietinum [73], Sesamum indicum [70], and other plant species [65,74].…”
Section: Discussionsupporting
confidence: 91%
“…Earlier studies revealed the role of PEG (in varying concentrations) in examining DS tolerance in sesame plants (Liang et al, 2021). However, only one report has evaluated sesame genotypes under DS (varying PEG concentration) using mutant plants at the seedling stage, establishing two sesame mutants "ML2-5" and "ML2-10" tolerant of severe DS (Kouighat et al, 2021). Very few molecular studies have been conducted in sesame under DS.…”
Section: Drought Stressmentioning
confidence: 99%
“…However, in arid and semi-arid areas, drought often occurs in conjunction with heat or high temperatures, which significantly impairs sesame productivity (Hassanzadeh et al, 2009). Adverse effects on seed yield and quality have been noticed when water stress occurs especially at germination and flowering stages (Hassanzadeh et al, 2009;Boureima et al, 2011;Komivi et al, 2016;Dossa et al, 2017;Kouighat et al, 2021). In Morocco, drought has always been present as a structural element of the climate, with increasing frequency in recent decades, due to climate change (Zraibi et al, 2011).…”
Section: Climate Change and Droughtmentioning
confidence: 99%
“…As a result, mechanized harvesting is impossible and commercial production will be limited due to costly labor (Langham and Wiemers, 2002). On the other hand, even though sesame is known as a drought-tolerant crop, it is susceptible during germination and flowering (Hassanzadeh et al, 2009;Boureima et al, 2011;Komivi et al, 2016;Dossa et al, 2017;Kouighat et al, 2021). Sesame cultivars grown in Morocco have wild traits including capsule dehiscence, long plant cycle, and sensitivity to biotic and abiotic stresses (El Harfi et al, 2021).…”
Section: Improvement Of the Existing Genetic Materialsmentioning
confidence: 99%